How do you solve (e-2)/2=(e+2)/3e22=e+23?

2 Answers
Aug 19, 2016

e=10e=10

Explanation:

(e-2)/2=(e+2)/3e22=e+23

or

3(e-2)=2(e+2)3(e2)=2(e+2)

or

3e-6=2e+43e6=2e+4

or

3e-2e=4+63e2e=4+6

or

e=10e=10

Aug 19, 2016

e=10e=10.

Explanation:

We rewrite the eqn. as (e+2)/(e-2)=3/2e+2e2=32, and, use a Result called

Compodendo Dividendo : a/b=c/d iff (a+b)/(a-b)=(c+d)/(c-d):ab=cda+bab=c+dcd

utilising this in our eqn. we get,

((e+2)+(e-2))/((e+2)-(e-2))=(3+2)/(3-2)(e+2)+(e2)(e+2)(e2)=3+232

(2e)/4=e/2=5 rArr e=102e4=e2=5e=10, as obtained by Deepak G. !